Pattern of management of febrile neutropenia among breast cancer patients treated with different chemotherapeutic regimens - S., Arun; Mohamedali, Seema P.; M., Anuradha (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Breast cancer is one of the common malignancies in females. Chemotherapy with Adriamycin and Cyclophosphamide (AC) followed by the Docetaxel (AC-T, Regimen-I), AC followed by Docetaxel and Carboplatin (AC-T+Cr, Regimen-II) and AC followed by Docetaxel and Trastuzumab (AC-T+Tr, Regimen-III) are commonly given for treatment. These cause myelosuppression and febrile neutropenia and need necessary interventions. Methods: This is a prospective open labelled observational comparative study to evaluate the antibiotic usage needed to treat sepsis following febrile neutropenia among breast cancer patients undergoing chemotherapy with regimen I, II and III. All patients received prophylactic Pegfilgrastim / Filgrastim. Antibiotics used and days in intensive care unit (ICU) in all the 8 cycles of chemotherapy were recorded. 38 patients in Regimen I, 40 patients in Regimen II and 46 patients in Regimen III completed the study and were included in the statistical analysis. Results: In regimen II, following cycle 2 of chemotherapy, none of the patients needed antibiotic therapy. Antibiotic use was maximum, following cycle 1of chemotherapy in regimen I and III, maximum number of antibiotics prescribed were 7. Number of days of ICU care needed for regimen II patients following 3rd cycle of chemotherapy was 3.5±3.5 days. No ICU care was needed for regimen III patients, following cycles 2, 3 and for regimen II following cycle 7. Conclusions: Febrile neutropenia produced by chemotherapy were effectively treated with intravenous antibiotics in ICU for an average of 2-3 days. No mortality was associated with febrile neutropenia and all patients were recovered.